Asymmetric gravitational lenses in TeVeS and application to the bullet cluster - Feix, Martin; Fedeli, Cosimo; Bartelmann, Matthias (Arxiv, 2007)
Aims: We explore the lensing properties of asymmetric matter density distributions in Bekenstein's Tensor-Vector-Scalar theory (TeVeS). Methods: Using an iterative Fourier-based solver for the resulting non-linear scalar field equation, we numerically calculate the total gravitational potential and derive the corresponding TeVeS lensing maps. Results: Considering variations on rather small scales, we show that the lensing properties significantly depend on the lens's extent along the line of sight. Furthermore, all simulated TeVeS convergence maps strongly track the dominant baryonic components, non-linear effects, being capable of counteracting this trend, turn out to be very small. Setting up a toy model for the cluster merger 1E0657-558, we infer that TeVeS cannot explain observations without assuming an additional dark mass component in both cluster centers, which is in accordance with previous work.